Records of the Colony and Plantation of New Haven: From 1638 To 1649, at 25-26 (Charles J. Hoadly ed., 1857) (enacted 1639) - (:unkn) unknown (My University, 1639)
Itt is ordered thatt every one that beares armes shall be compleatly furnished wth armes (viz), a muskett, a sworde, bandaleers, a rest, a pound of powder, 20 bullets fitted to least, and be ready to show them in the markett place vpon Munday the 16th of this Moneth before Captaine Turner and Leivtennant Seely vnder the pena
Keywords: REQUIRED POSSESSION